THE EFFECT OF CREDIT RATING ANNOUNCEMENT TO MARKET REACTION - Zega, Eunike .; Massie, James D.D; Tasik, Hizkia H.D (Universitas Sam Ratulangi, 2017)
Abstract: Credit assessment for sovereign is generally done by a Credit Rating Agency such as Standard & Poor’s that increase Indonesia rank as a good news for the investment sector in Indonesia, also firm’s variables such as size used for trading strategies that can outperform the market. This study aims to analyze the market reaction to the announcement of Indonesia Investment Grade. The method that used is event study methodology. Sample used 22 companies of LQ 45 in IDX. Analysis using the 7-days window period with daily stock price and market index. The expected return calculated by market model. T-Test be used to examine the significance of Average Abnormal Return around the announcement. The results of the study is there is a significant abnormal return the day after the announcement of Investment Grade. Another aims in this research is to analyze is whether firm size related to market reaction. The data used is daily market capitalization. The method used is three panel data model : Pooled Model, Fixed Model, and Random Model. Throughout the three models, the firm size hypothesis has positive significant relationship on abnormal return. Findings suggest to extend the sample thus able to reflect Indonesian capital market. Keywords: credit rating (investment grade) announcements, event study methodology, abnormal return, firm size, panel data, market reaction